Design of Speed Limiter Display For Uwin Fly Electric Bike Based on Internet of Things: Perancangan Speed Limiter Display Sepeda Listrik Uwin Fly Berbasis Internet of Things - Pramana, Joko; Saputra, Dwi Hadidjaja Rasjid; Syahrorini, Syamsudduha (Procedia of Engineering and Life Science, 2023)
To contribute to the development of electric vehicle technology in Indonesia, a data monitoring system has been designed to monitor and remotely control the condition of electric motorcycles. The device is designed using a nodeMCU ESP8266 microcontroller, voltage sensor, switch, button, Hall sensor, and buzzer. Data is processed and displayed on Blynk. Experiments were conducted on battery monitoring, speed, speed mode, crush control, and speed limiter alarms. Implementing the device on the Uwin Fly electric bicycle can serve as a reference for the feasibility of the device on other electric bicycles. Additionally, the development of electric bicycle monitoring displays and speed limiter features can increase awareness among electric bicycle users, especially mothers and children. Overall, the monitoring system could contribute to enhancing the safety and efficiency of electric motorcycles on the roads of Indonesia.Meanwhile, if the article is written in English, the abstract should be typed in English only. The abstract should be typed as concisely as possible and should be composed of: problem statement, method, scientific finding results, and a short conclusion. The abstract should be typed in one paragraph only and two-columns format. All sections in the manuscript should be typed using Times New Roman font. Authors should use this document as their article template.